Method of optimization of decision-making during management of safety of flights in the activities of operators of aerodromes - S. A. Tolstykh (Научный вестник МГТУ ГА)
In modern conditions of limited budget for enterprises of aerodrome operators, the task of optimizing decision making in flight safety management is becoming extremely urgent. Management decisions, which are a safety management tool, must be not only effective in terms of expected improvements in safety, but also cost-effective and appropriate for the enterprise. Optimization in this article should be understood in terms of the mentioned criteria. The article presents a method for supporting management decision-making as part of a safety management strategy for the activities of aerodrome operators. In the presented methodology, an important place is given to indicators of the level of safety of flights and their use in making managerial decisions. Along with the safety indicator, an indicator of financial damage from recorded events is used, which is calculated in value terms taking into account direct and indirect damage to the aerodrome operator. Regression modeling is used in conjunction with the decision-making technique of “human-machine procedures”. Regression analysis is performed using STATISTICA software, and allows you to identify the dependence of indicators on the degree of influence of hazard factors. The resulting model, based on data from last year, makes it possible to forecast the values of indicators for the next. Using the decision-making methodology of “human-machine procedures”, an assessment is made of the priority of implementing managerial decisions based on an integrated criterion. The methodology ensures compliance with the requirements of Russian and international air legislation for operators of certified aerodromes. The scope of its application can be expanded to SMS of all aviation service providers, taking into account the relevant specifics of the services provided and the existing hazard factors.